2005
DOI: 10.1089/aid.2005.21.207
|View full text |Cite
|
Sign up to set email alerts
|

SPL7013 Gel as a Topical Microbicide for Prevention of Vaginal Transmission of SHIV89.6Pin Macaques

Abstract: SPL7013 is a dendrimer with a polyanionic outer surface that allows multiple interactions with target sites. It potently binds and blocks HIV-1 and chimeric simian/HIV-1 viruses (SHIVs) replication in vitro. Gels containing different concentrations of SPL7013 were used as topical microbicides in female pigtailed macaques (Macaca nemestrina) to study their ability to prevent vaginal transmission of SHIV(89,6P). On virus challenge, all untreated macaques (8/8) and seven of eight macaques treated with placebo gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 22 publications
2
117
0
2
Order By: Relevance
“…Another group of four macaques were not pretreated with DMPA prior to virus challenge. Two macaques in each group were inoculated intravaginally with 500 TCID 50 of RT-SHIV; the remaining two macaques in each group received 1,000 TCID 50 as previously described [13,14]. Briefly, 0.5 ml of virus preparation was atraumatically introduced to the vaginal mucosa using a stainless steel animal feeding tube.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group of four macaques were not pretreated with DMPA prior to virus challenge. Two macaques in each group were inoculated intravaginally with 500 TCID 50 of RT-SHIV; the remaining two macaques in each group received 1,000 TCID 50 as previously described [13,14]. Briefly, 0.5 ml of virus preparation was atraumatically introduced to the vaginal mucosa using a stainless steel animal feeding tube.…”
Section: Methodsmentioning
confidence: 99%
“…SIVmac239 gag -specific primers were used to amplify virus DNA by PCR as described previously [13,14,46]. …”
Section: Methodsmentioning
confidence: 99%
“…[134] A 3 wt% formulation has shown to possess inhibitory activity against HIV-1 and the herpes simplex virus (HSV) up to 3 h following vaginal administration in women demonstrating long-lived efficacy of the dendritic drug. [135] Although other polymers such as poly(naphthalene sulfonate) (5, PRO2000), [76] carrageenan [136] and cellulose sulfate [137] based microbicides showed promising results in vitro, human trials demonstrated that these gels did not provide protection against HIV-1 infection.…”
Section: Applications and Perspectives Of Anti-hiv Polymer Therapeuticsmentioning
confidence: 99%
“…As far as dendrimers are concerned, their applications in treatment of several human diseases are under critical investigation and looks very promising; these macromolecules serve as targeted drug, carriers and delivery agents as well as imaging agents in human systems [4][5][6]. In particular, polymers having a dendrimer-based structure have emerged from several research programs focused on the development of inhibitors of HIV and other enveloped viruses [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: IImentioning
confidence: 99%